An Argument for the Test of Proportionality in Concreto: Silenced Voices from the Margins to the Center - Clérico, Laura; Aldao, Martín (Springer Science and Business Media B.V., 2021)
As a four-step exam, proportionality has become a well-known technique of rights adjudication. Moreover, we claim, among others, that as a framework for argumentation, and through modulation, it can be used in a manner that enables courts to compensate structural inequality patterns, allowing the voices and claims of people in situations of vulnerability. In order to corroborate our thesis, we contrast the application of proportionality by majority and minority votes in a case ruled by the ECtHR about the right of a woman to choose her residence. While both draw upon the exam, the first one opts for a general approach rendering invisible the intersectional layers of discrimination (poverty and gender) that undermines the applicant standing. On the contrary, the dissenting opinion opts for a thorough test (in concreto) able to account for the poverty and gender dimensions of the case. In doing so, we show the potentiality of the test of proportionality in concreto that allows questioning already established categories by empowering marginalized voices, and lays a clear path on how to deal with that process.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Argumentative empowerment; Concrete approach; Gender and poverty; General approach; Proportionality

Argentina: Strong linkage between IHRL and domestic law - Clérico, Laura; Novelli, Celeste (Edward Elgar Publishing Ltd., 2021)
This chapter examines the implementation and compliance with International Human Rights Law in Argentina. To attain that objective, this work takes into consideration the leading role of Argentina related initially to the investigation and prosecution of gross human rights violations committed during the last military dictatorship, and which has certainly contributed to the development and strengthening of the Inter-American System in the region. This is the point of departure for analyzing the strong linkage between international human rights law and national law that was reinforced by the constitutionalisation of the main human rights declarations and treaties since. We sustain that this linkage could not have happened without case law giving meaning to this linkage. Besides human rights movements, organizations, and defenders in accordance with the decisions of international human rights bodies have contributed to the strengthening and the effectiveness of human rights norms and their compliance, as well as some coalitions among Legislative, Executive and Judicial Power, which have converted the respect of human rights law into a matter of state policy. Additionally, the work explores the procedures, institutions and practices developed by federal and provincial structures in order to guarantee the implementation of supranational rulings, especially the decisions taken by the Inter-American Court and the Inter-American Commission of Human Rights. Finally, this works outlines the significant role of human rights organizations and victims in litigating and monitoring compliance concerning the protection of human rights in Argentina.
CRIS-Team Scopus Importer:2023-03-21

Conceptions and Frameworks: Key Trends on the Rule of Law in Latin America - Aldao, Martín; Clérico, Laura (Diritto Pubblico Comparato ed Europeo, 2023)
CRIS-Team Scopus Importer:2024-06-28
Keywords: human rights; Latin America; multidimensional inequality; rule of law; social rule of law

Discrimination Based on Sexual Orientation and Social Security Rights in the Case Law of the IACtHR and the ECtHR. A Tale of Divergences? - Clérico, Laura (Revista de la Facultad de Derecho, 2019)
For some years now, universal and regional human rights protection systems converge in the extension of the grounds for prohibiting discrimination, as in the case of sexual orientation. However, a micro-study of the similarities and divergences in the equality test for differentiated treatment by social orientation in the access to social security rights, demonstrate the divergences between the Inter-American Court and the ECtHR. Thus, this paper argues that the ECHR assumes a conditioned incrementalit approach regarding the recognition of LGBTI rights against the categorical approach of the Inter-American Court as a speed adopter. The lack of a factual European consensus on the claim and the granting of a wide margin of state appreciation gain primacy in the face of the equality test in the ECtHR. On the contrary, the IACtHR applies an examination of intensive equality if the differential treatment is based on the sexual orientation of the persons although there is no Inter-American consensus on the subject. The article concludes thus differentiating two types of human rights adjudication approach.
CRIS-Team WoS Importer:2019-09-13

Equal protection - Clérico, Laura; Ronconi, Liliana; Aldao, Martín (Taylor and Francis, 2016)
This chapter describes some of the developments occurring in the region and, in particular, to highlight the questions that the inter-American system and local courts have asked throughout this process. For a large part of the Latin American experience, criminal justice seems to express a relevant manifestation of the aspiration of justice for a violent past. Criminal prosecution is, perhaps, the most direct, problematic, and debated tool in a transitional context. Transitional justice also recognizes the rights of victims of systematic human rights violations and the right to effective and adequate reparations. Reparations help to prevent the recurrence of violations and can be aimed both at individuals as well as communities or groups of people. According to the Inter-American Commission on Human Rights, reparations tend to erase the effects of past violations, which is why their nature and amount should depend on the material and immaterial damage caused.
CRIS-Team Scopus Importer:2023-03-21

IMF’s Surcharges as a Threat to the Right to Development - Bohoslavsky, Juan Pablo; Cantamutto, Francisco; Clérico, Laura (Development, 2022)
This article focuses on the implications of the IMF’s surcharges policies, jointly with its de facto preferred creditor status, on the right to sustainable development of sovereign borrowers. The article argues that, while surcharges are not effective in limiting access to IMF credit, they inequitably distribute the IMF’s operating costs, are disproportionate, pro-cyclical, very costly for developing countries, and non-transparent. Furthermore, if surcharges are theoretically a way to protect the IMF from potential risks of default, the article questions the IMF’s de facto preferred creditor status, as it precisely denies the possibility of granting debt relief in case of insolvency, ultimately affecting the right to development of —mainly— middle-income borrowing countries.
CRIS-Team Scopus Importer:2022-09-09
Keywords: Developing countries; Global Finance; Human Rights; Multilateral Loan Conditions; Preferred Creditor Status

Proportionality and criminal law in the Interamerican-System - Clérico, Laura (Nomos Verlagsgesellschaft mbH und Co KG, 2023)
This essay aims to explore the uses of proportionality when criminal law interferes with human rights in Latin America. To do so, I use the case law of the Interamerican Court of Human Rights ("IACtHR") as an exemplary basis to demonstrate the various uses of proportionality, to focus on its use in challenging criminal law and criminal sanctions. As I will show, the proportionality test is a methodology that forms part of the consolidated jurisprudence of the IACtHR and this has relevance for the Inter-American system because of the impact that the Court's standards seek to have at the domestic level.
CRIS-Team Scopus Importer:2024-12-16

Proportionality in social rights adjudication: Making itworkable - Clérico, Laura (Springer International Publishing, 2018)
This paper supports the idea that the proportionality test works as an analytical framework in adjudicating social rights. In particular, suitability and alternative means tests should gain relevance and stop being the neglected steps of the proportionality test. Suitability and alternative means tests are reinforced by considering several aspects, such as quantitative, qualitative and probabilistic. In this vein, it serves to rebut the position which sustains that proportionality as a safeguard against the state not doing enough is pure balancing. Suitability and alternative means tests state what has been done and what is possible to be done to promote the social rights in question. In sum, the work shows that this basic structure of proportionality can be used as an analytical tool to reconstruct decisions about social rights adjudication. Therefore, there is no reason for the Courts not to make more systematic use of the three-part test of proportionality, at least seen from the analytical level.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Prohibition ofinsufficiency; Proportionality; Social rights adjudication; Suitability test; Test of alternative means

The argument of the lack of regional consensus on human rights: Divergence between the ecthr and the iacthr El argumento de la falta de consenso regional en derechos humanos: Divergencia entre el tedh y la Corte IDH - Clérico, Laura (Revista Derecho del Estado, 2020)
This work analyzes a central argument in the ecthr that combines the absence of a European consensus with a wide margin of appreciation for the State. The complexities of this constellation are usually obscured when some States of the Inter-American region advocate its importation. To this end, it is proposed to distinguish different uses of consensus, as well as the descriptive and normative function of the argument, and the relationship between the existence or absence of the European consensus and the determination of the margin of appreciation of the State. These complexities allow to accurately determine the divergence between the ecthr and the iacthr in the use of the lack of regional consensus in the constellation of cases related to discrimination based on sexual orientation, as well as to propose various hypotheses that explore the divergence. All this argumentative path allows to continue supporting the thesis about the divergent argumentative profiles of the regional courts that is determined by their audiences: the ecthr, as a court concerned by the interlocutors, the States of the region, in front of the iacthr as a court concerned with evaluating the (un)reasons for the restrictions on rights, beyond the (un) pleasure of the States of the region.
CRIS-Team Scopus Importer:2020-07-03
Keywords: Argumentative approach of the echtR and the iacthr; Discrimination based on sexual orientation; Divergences; Lack of European consensus; Lack of Inter-American consensus

The right to dignified living conditions and the situation of vulnerability in the decisions of the Inter-American court Derecho a condiciones de existencia digna y situación de vulnerabilidad en la jurisprudencia de la corte InterAmericana - Beloff, Mary; Clérico, Laura (ESTUD CONST, 2016)
In this work we argue that the jurisprudential development of the right to dignified life and the subsequent affirmative obligations of the State to generate conditions lie in the argument of material equality. In order to support our thesis, we reconstruct the argumentative strategy that departs from the affirmative nature of the right to life. Later, we reconstruct the strategy for justifying it under ESCR rights. We highlight that neither of them are excluded to determine the content of the right of dignified life. The (in) sufficiency of the conditions of decent living is evaluated under the light of social, cultural, and economic rights: the right to access to water, to food, to health, and to education. Finally, we argue for the benefits of the material equality approach. At the same time, it allows us to discuss the advantages and disadvantages of the use of vulnerable groups or situation of vulnerability arguments with regards to the obligation of generating conditions for a decent life.
CRIS-Team Scopus Importer:2023-03-21
Keywords: ESCR positive obligations; Material equality; Right to dignified living conditions; Vulnerability

Towards an integral analysis of stereotypes: Challenging the standard guarantee of impartiality Hacia un análisis integral de estereotipos: Desafiando la garantía estándar de imparcialidad - Clérico, Laura (Revista Derecho del Estado, 2018)
The use of stereotypes to the detriment of the discriminated group should imply questioning the standard guarantee of judicial impartiality. Even taking the analysis of stereotypes seriously, the depth of its consequences has not been sufficiently taken into account in the constitutional and human rights argumentation because it has not challenged with all intensity the standard way in which the guarantee of impartiality is conceived and applied in legal practice and even by the regional court for the protection of human rights. I will defend two central theses: (1) the use of stereotypes necessarily impacts on the analysis of the guarantee of impartiality and (2) impartiality must get rid of the presumption of impartiality.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Argumentation in constitutional law and human rights; Gender; Impartiality; Stereotypes; Structural inequality

Violence against women in the production of the Inter-American comission and the Inter-American court of human rights La violencia contra las mujeres en las producciones de la comisión y la corte interamericana de derechos humanos - Clérico, Laura; Novelli, Celeste (ESTUD CONST, 2014)
This article aims to identify and analyze the legal standards built by the Inter-American Commission and Inter-American Court of Human Rights on the following topics: the definition of violence against women/gender violence; the legal description of the actions or omissions that constitute a breach to human rights and which are also an expression of gender inequality; obligations and appropriate means of reparations owed by States to eradicate gender violence. The analysis finds progress on gender mainstreaming in the productions of the Inter American System of Human Rights, but also a narrow conception of violence against women focused mainly on sexual violence. This approach leaves out many other important aspects. Furthermore, this paper warns about the emphasis on access to justice as a reparatory measure that difficult to consider the implementation of other adequate actions towards the eradication of violence against women.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Access to Justice; Inter American Commission; Inter American Court; Inter American System of Human Rights; Violence against women